Tick-borne relapsing fever Borreliosis, a major public health problem overlooked in Senegal - Ndiaye, El Hadji Ibrahima (PLoS Negl Trop Dis, 2021)
BACKGROUND: Tick-borne relapsing fever (TBRF) is the most common vector-borne bacterial disease in humans in West Africa. It is frequently clinically confused with malaria. Our study aims to determine, on a micro-geographic scale, the conditions for the maintenance and spread of TBRF in the Niakhar district of Senegal. METHODOLOGY/PRINCIPAL FINDINGS: We conducted clinical, entomological and animal reservoir investigations. Field surveys were carried out in order to investigate the presence of Ornithodoros sonrai vector ticks and to detect Borrelia spp. by qPCR using the 16S rRNA and glpQ genes, respectively. Micromammal trapping series were carried out inside homes and Borrelia infection was detected using brain tissue qPCR. Capillary blood samples from febrile patients were also tested for Borrelia using qPCR. More than 97% (40/41) of the villages surveyed were infested with O. sonrai ticks. The prevalence of Borrelia spp. infections in ticks was 13% (116/910), and over 73% (85/116) were positively confirmed as being Borrelia crocidurae. Borreliosis cases accounted for 12% (94/800) of episodes of fever and all age groups were infected, with children and young people between the ages of 8–14 and 22–28 being the most infected by the disease (16% and 18.4%). TBRF cases occurred in all seasons, with a peak in August. In two species of small rodents that were found to be infected (Arvicanthis niloticus, Mus musculus), the proportion of Borrelia infection was 17.5% (10/57), and the highest prevalence of infection (40.9%, 9/22) was observed in A. niloticus. CONCLUSION/SIGNIFICANCE: Our study indicates that TBRF is an endemic disease in the Niakhar district, where children and young people are the most infected. Arvicanthis niloticus and O. sonrai ticks are massively present and appear to be the main epidemiological reservoirs causing its extensive spread to humans.